The landscape of biofilm models for phage therapy: mimicking biofilms in diabetic foot ulcers using 3D models - Martinet, Mark Grevsen; Thomas, Marvin; Bojunga, Jörg; Pletz, Mathias W.; Vehreschild, Maria J. G. T.; Würstle, Silvia (Frontiers in Microbiology, 2025)
Diabetic foot ulcers (DFU) affect up to 15–25% of patients suffering from diabetes and are considered a global health concern. These ulcers may result in delayed wound healing and chronic infections, with the potential to lead to amputations. It has been estimated that 85% of diabetes-related amputations are preceded by a diagnosis of DFU. A critical factor in the persistence of this disease is the presence of polymicrobial biofilms, which generally include Staphylococcus aureus, Pseudomonas aeruginosa, and Escherichia coli. The involvement of diabetic comorbidities such as ischemia, hyperglycemia, and immune-compromised status creates a perfect niche for these bacteria to evade the body’s immune response and persist as biofilms. Bacteriophage therapy can target and lyse specific bacteria and is emerging as an effective treatment for biofilm-related infections. While this treatment shows promise in addressing chronic wounds, our current models, including animal and static systems, fail to capture the full complexity of DFU. Innovative approaches such as 3D bioengineered skin models, organoid models, and hydrogel-based systems are being developed to simulate DFU microenvironments more accurately in 3D without using ex vivo or animal tissues. These advanced models are critical for evaluating bacteriophage efficacy in biofilm-associated DFU, aiming to enhance preclinical assessments and improve therapeutic outcomes for DFU patients.